2020
DOI: 10.2147/ott.s229614
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Downregulation of miR-575 Inhibits the Tumorigenesis of Gallbladder Cancer via Targeting p27 Kip1</p>

Abstract: Background: Gallbladder cancer (GBC) is the most common biliary tract malignant cancer worldwide. It has been reported that microRNA-575 (miR-575) was involved in the tumorigenesis of many cancers. However, the role of miR-575 during the progression of GBC remains largely unknown. Methods: The expression of miR-575 in GBC cells was detected by quantitative real-time polymerase chain reaction. The proliferation of GBC cells was examined by CCK-8 assay and Ki-67 staining. Apoptosis of GBC cells was measured by f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Abnormal expression of miR-575 may lead to cancer development. Previous studies indicated that miR-575 plays an oncogenic role in promoting cell proliferation, migration and invasion in NSCLC, HCC and gallbladder cancer [22,43,44]. In contradiction to these results, miR-575 overexpression FOXM1 is a transcriptional factor that plays a pivotal role in cancer development.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Abnormal expression of miR-575 may lead to cancer development. Previous studies indicated that miR-575 plays an oncogenic role in promoting cell proliferation, migration and invasion in NSCLC, HCC and gallbladder cancer [22,43,44]. In contradiction to these results, miR-575 overexpression FOXM1 is a transcriptional factor that plays a pivotal role in cancer development.…”
Section: Discussionmentioning
confidence: 84%
“…Abnormal expression of miR‐575 may lead to cancer development. Previous studies indicated that miR‐575 plays an oncogenic role in promoting cell proliferation, migration and invasion in NSCLC, HCC and gallbladder cancer [22,43,44]. In contradiction to these results, miR‐575 overexpression significantly inhibited migration, proliferation and angiogenesis as well as induction of apoptosis of HUVEC by targeting the Rab5/MEK pathway, indicating that miR‐575 plays a tumor suppressor role in HUVEC [45].…”
Section: Discussionmentioning
confidence: 86%
“…MiR-575 increased proliferation and inhibited apoptotic death of gastric cancer cells by regulating PTEN both in vitro and vivo [ 36 ]. Knockdown of miR-575 significantly suppressed proliferation and invasion of gallbladder cancer (GBC) cells via targeting p27 Kip1 [ 37 ]. Overexpression of lncRNA MIR31HG decreased the expression of miR-575 by targeting ST7L, which acted as a tumor suppressor in hepatocellular carcinoma [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with miR-181b/d potentially having tumor suppressive roles in PDAC. Although miR-575 has not been previously linked to PDAC, it has been implicated in development of other gastrointestinal cancers, such as gastric cancer via inhibition of PTEN [25], biliary cancer via inhibition of p27Kip1 [26], and hepatocellular carcinoma via inhibition of ST7L [27]. Interestingly, in our study, miR-575 decreased expression was associated with higher risk score and recurrence; it is possible that miR-575 may have disparate tissue-specific functions and that its downregulation is secondary to upregulation of other pathways that mediate PDAC recurrence.…”
Section: Discussionmentioning
confidence: 99%